140k views
2 votes
F(x) = 3x² - 2x

g(x) = x + 4
When finding f(x) · g(x), what could the first step look like?

User Krousey
by
5.3k points

1 Answer

2 votes

Answer: look at the picture

Step-by-step explanation: Hope this help :D

F(x) = 3x² - 2x g(x) = x + 4 When finding f(x) · g(x), what could the first step look-example-1
F(x) = 3x² - 2x g(x) = x + 4 When finding f(x) · g(x), what could the first step look-example-2
F(x) = 3x² - 2x g(x) = x + 4 When finding f(x) · g(x), what could the first step look-example-3
User Vkharb
by
6.0k points